Why hasn't this woman been screened for breast and cervical cancer? – Evidence from a Chinese population-based study. (March 2019) - You, H.; Gu, H.; Zhang, N.; Fan, H.; Kou, Y.; Cui, N.; Liu, X.Y.; Li, X.L.; Gu, J.H.
Abstract: Objective: Less than half of eligible Chinese rural women have been screened for breast and cervical cancer. The objective of this study was to describe individual-level reasons for attending or not attending 'two cancers' screening using Andersen's Behavioral Model of Health Services Use. Study design: Cross-sectional study. Methods: The study sample was from the Health Services Survey in 2013 in Jiangsu, China. A total of 6520 rural women aged 36–65 years answered the questions on 'two cancers' screening participation and were included in the final analysis, which consisted of univariate and multivariate logistic regression. Results: In the results of multivariate logistic regression, factors significantly associated with having 'two cancers' screening included educational level (odds ratio [OR] = 0.78, 95% confidence interval [CI] = 0.65–0.92), per capita household income (OR = 0.65, 95% CI = 0.58–0.73), availability of female medical faculty in township facilities (OR = 0.35, 95% CI = 0.28–0.42), quality of life (OR = 0.72, 95% CI = 0.58–0.90), being nulliparous (OR = 3.21, 95% CI = 1.96–5.26), and multiparous (OR = 1.91, 95% CI = 1.68–2.16). Conclusion: To reduce inadequate screening service utilization of breast and cervical cancer in rural areas, efforts should be made not only to target the vulnerable rural women with lower income, lower educational level, and lower health conditions but also to further improve access to female primary-care providers. Strategies are also urgently needed to focus on nulliparous and multiparous women. Highlights: Despite the availability of screening programs, many eligible women are not screened for breast and cervical cancer. Screening rate is lower among vulnerable rural women with low social economic and health status than the rest. Availability of female primary-care providers in grass-roots level was found to be correlated with screening attendance. Multiparous women are less likely to adhere to the screenings than primiparous women in China.